CRIME STUDY IN POSTMODERNISM PERSPECTIVE - Herry Fernandes Butar Butar (Polteknik Ilmu Pemasyarakatan, 2020)
This research answers how Postmodernism criminology explains about conceptual meaning of crime that differed from modern perspective. With the development of criminology and the rise of new thought in criminology gave us chance at renewing the approach in doing research needed to explain crime and how crime occurred. In post-modernism criminology that has been critically question that modern perspective had not been explained crime as how crime defined empirically. The research is using qualitative perspective with literature study and case study of crime such as environment crime, womanizing, the rise of sentencing in Indonesia and other cases and analysing it with the perspective of post-modern criminology. The case study goals are how to see crime from postmodern and modern criminology and gave the option how to create policy to handle crime